Recrystallization and related annealing phenomena - Humphreys, F. J. (Elsevier, 2004)
Related Annealing Phenomena fulfils the information needs of materials scientists in both industry and academia. The subjects treated in the book are all active research areas, forming a major part of at least four regular international conference series. This new 2nd edition ensures the reader has access to the latest findings, essential to those working at the forefront of research in universities and laboratories. For those in industry, the book highlights applications of the research and technologically important examples. In particular, the 2nd edition builds on the significant progress made recently in the following key areas: Deformed state, including deformation to very large strains Characterisation of microstructures by electron backscatter diffraction (EBSD) Modelling and simulation of annealing. Continuous recrystallization. * Fully revised and up-to-date, the 2nd edition highlights the significant progress made recently in this important area of research * Detailed coverage, much more comprehensive treatment than is found in textbooks on physical metallurgy bridges the gap between theory and practice by examining the application of quantitative, physically based models to metal forming processes.